Big Data-Based Frameworks For Personalized Healthcare - Dhruvit kumar Patel; Priyam Vaghasia (Educational Administration: Theory and Practice, 2024)
Advancement in technologies related to big data has influenced the delivery of healthcare in a major way the world over, and this has led to the emergence of health care frameworks that are personalized. These frameworks use huge amount of data from different sources, such as EHRs, genomics, wearable, devices, and patient reported outcomes to provide personalized healthcare services. Personalized healthcare that incorporates big data includes sophisticated data which helps in the diagnosis of health problems and in the formulation of treatment as well as disease prevention strategies. Big data based frameworks help the healthcare providers to go beyond the conventional approach of ‘this formula fits everyone’ allowing a customised approach that takes into account of a person’s specific genetic and physical make-up and the environment he/she is exposed to. Machine-learning algorithms and artificial intelligence (AI) have central and critical roles in these frameworks because they provide predictive information about disease and therapy risks and benefits. In addition, they help patient tracking at all times, prompt decision-making, and search for new biomarkers for the early diagnosis of the disease. Nevertheless, applying big data based on Personalized Healthcare architectures has some issues, such as, for instance, confidentiality questions, data structure non-uniformity, data heterogeneity, and data source integration issues. Also, the issue of ethics needs to be discussed when collecting the result-sensitive health information to protect patients’ information and their trust. However, all these challenges of personalised healthcare have been considered as strengths of the personalised medicine due to the following advantages; high patient’s quality of life, lesser costs of healthcare than traditional medicine and better patient results. This abstract briefly states the main milestones of the big data-centric frameworks for the individualized approach in the context of the modern healthcare sphere improvement. As the volume and variety of big data rise, and healthcare turns out to be more intricate, such frameworks will prove indispensable in providing bespoke, high-quality care to patients.